Financial Anomalies: Examination of Chinese Bâ€share Markets from 1993 to 2006 - Su, Roger; Zhao, Ying; Huang, Hedy Jiaying (Asian Journal of Business and Accounting, 2017)
This study investigates the financial anomalies on the Chinese Shanghai Bâ€share (SHB) and Shenzhen Bâ€share (SZB) markets from 1993 to 2006 by using valueâ€weighted data and equalâ€weighted data. Before February 2001, the Bâ€shares could be traded by only foreign investors. However, in February 2001, the Chinese investors were allowed to invest in the Bâ€share market. When both unadjusted valueweighted data and unadjusted equalâ€weighted data are used, the study reveals there is the March effect after February 2001 in both SHB and SZB markets; however, there is no evidence of the March effect from the adjusted valueâ€weighted and adjusted equalâ€weighted data for the same period. Our study shows that the high March market return was attributable to an unusual return in March 2001 which can be explained by the influx of funds due to the opening of the Bâ€share markets to domestic investors. Thus, we do not find clear evidence of seasonality in the Chinese Bâ€share markets. Nevertheless, the analysis on the adjusted equalâ€weighted data finds a size effect in the Shenzhen Bshare market â€“ the smallestâ€size group shows a significant January effect in the period from 2001 to 2006; which supports Reiganum (1983) that the January effect is largely a small capitalization phenomenon. Our findings may influence the investment behaviour of overseas investors. Keywords: Chinese Bâ€share Market, Efficient Market, Seasonalities, Financial Anomalies